Pemberdayaan Masyarakat dalam Perencanaan dan Implementasi Ekodrainase Di Desa Cibodas, Kecamatan Pasir Jambu, Kabupaten Bandung - Yanidar, Ramadhani; Winarni, Winarni; Yulinawati, Hernani; Yuslim, Silia (Jurnal Sinergitas PKM & CSR, 2022)
Cibodas Village, Pasir Jambu District, Bandung Regency is in the upstream area in the Ciwidey sub-watershed area, which is one of the sub-watersheds in the Citarum watershed.  The principle of Eco drainage as a way in water conservation needs to be applied in this region. Community Service activities in the context of community empowerment in the planning and implementation of Eco drainage began with providing a basic understanding and technical properties of Eco drainage infrastructure and continued with piloting Eco drainage design for village governments, and community mobilizers to be able to implement Eco drainage in managing rainwater runoff. The community empowerment method consists of 3 stages, namely the coordination stage with partners and field surveys, preparation, and implementation of PkM. Coordination activities as a collaborative in building partnerships can run well. This can be seen from the full support of the Village Head, BumDes Chairperson, and the participation of village government officials both through initial coordination, field surveys to community involvement in planning a pilot infiltration structure design as an application of Eco drainage in the courtyard of the RW-04 office which also functions as a Pos Posyandu. Increased capacity and being self-sufficient in the application of Eco drainage are expected to be sustainable to all village communities. It expected the result will provide a multiplier effect in transforming Cibodas Village into an Ecovillage Village for the sustainability of the Citarum River as a water resource, since enable to play a role in the management of the Ciwidey watershed and the Citarum watershed in general. Abstract in BahasaDesa Cibodas, Kecamatan Pasir Jambu, Kabupaten Bandung berada di daerah hulu di wilayah sub-DAS Ciwidey, yang merupakan salah satu subDAS yang berada dalam DAS Citarum. Pengelolaan sumber daya air dengan menerapkan prinsip ekodrainase sebagai salah satu cara dalam konservasi air perlu diterapkan di wilayah ini. Metode pemberdayaan masyarakat terdiri dari 3 tahap yaitu tahap koordinasi bersama mitra dan survey lapangan, persiapan dan pelaksanaan PkM. Kegiatan koordinasi sebagai upaya kolaboratif dalam membangun kemitraan dapat berjalan dengan baik. Hal ini dapat terlihat dari dukungan penuh dari Kepala Desa, Ketua BUMDes serta partisipasi aparat pemerintah desa baik melalui koordinasi awal, survey lapangan hingga pelibatan masyarakat dalam merencanakan percontohan desain bangunan resapan sebagai penerapan ekodrainase di halaman Kantor RW04 yang sekaligus juga berfungsi sebagai Pos Posyandu. Kegiatan Pengabdian kepada Masyarakat (PkM) bertujuan untuk meningktkan kapasitas masyarakat dalam perencanaan dan implementasi ekodrainase dimulai dengan memberikan pemahaman dasar serta sifat teknis infratruktur ekodrainase dan dilanjutkan dengan percontohan desain ekodrainase bagi pemerintah desa, dan penggerak masyarakat agar dapat menerapkan ekodrainase dalam mengelola limpasan air hujan. Pemberdayaan serta kemandirian dalam penerapan ekodrinase diharapkan dapat berkelanjutan kepada seluruh masyarakat desa, sehingga mampu memberikan multiplier efek dalam mewujudkan Desa Cibodas menjadi Desa Ecovillage, sehingga dapat berperan dalam pengelolaan DAS Ciwidey pada khususnya dan DAS Citarum pada umumnya, untuk keberlanjutan sumber daya air Sungai Citarum.